Pengembangan Website Company Profile untuk Meningkatkan Promosi Digital PT Multi Global - Jolie, Angelina (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
In the face of digital era promotional challenges, developing a company profile website has become a crucial need for PT Multi Global. Despite operating for over two decades, the company has lacked a formal promotional platform capable of reaching a broader market. Previous promotional efforts relied solely on word-of-mouth, which is limited in expanding the company’s visibility in today’s digital landscape. Through a Community Service (PkM) initiative, this study aims to design and develop an informative and responsive company profile website using WordPress CMS and the Elementor plugin. The development process follows the System Development Life Cycle (SDLC) method with a waterfall approach, encompassing requirements analysis, design, implementation, testing, and maintenance phases. The final outcome of this project is a website that provides comprehensive information about the company, its products, and services, while also enhancing brand awareness and facilitating easier access to information for customers. This website development is expected to serve as an effective solution in supporting PT Multi Global's business growth and boosting the company’s competitiveness in an increasingly competitive market.